Pelatihan Media Ajar Interaktif Berbasis Teknologi bagi Guru Bahasa Inggris di SDN 1 Mojoagung - Tenika Illananingtyas; Syaifudin Zuhri (STAI Senori Tuban, 2026)
Digital transformation in education requires teachers to integrate technology-based learning media into the teaching and learning process. The limited ability of teachers to develop technology-based instructional media has become an obstacle to English language teaching at the elementary school level. Interactive learning media are needed to increase students’ motivation and engagement; however, they have not been optimally utilized by teachers. This Community Service Program aims to improve the competence of English teachers at SDN 1 Mojoagung in designing and developing technology-based interactive instructional media that are appropriate to the characteristics of elementary school students. The method employed is practice-based training conducted through several stages: (1) needs analysis to identify teachers’ initial competencies and the types of media required; (2) delivery of theoretical material on the concepts of interactive instructional media and the use of educational technology; (3) hands-on workshops on developing digital instructional media using interactive learning applications; (4) guided implementation, in which participants independently develop instructional media under the guidance of the team; and (5) online mentoring and evaluation to provide feedback and ensure the sustainability of media implementation in the classroom. The results indicate an improvement in teachers’ ability to design and produce interactive instructional media, as well as increased motivation and readiness to integrate technology-based media into English language teaching at the elementary school level